THU0367 The influences of non-steroidal anti-inflammatory drugs on serum VEGF and BMP-2 levels in patients with axial spondyloarthritis. (15th June 2017) - Gao, G; Lu, L; Li, Z; Li, Y
Abstract : Background: VEGF has been found abnormal in patients with SpA and related to disease activity [1, 2]. BMP-2 has a function of promoting the osteophyte formation, and may be involved in the integration process of AS spine [3, 4]. VEGF and BMP-2 interact with each other, participating in the formation of osteoblast [5]. COX-2 works together with the expressions of BMP2 and VEGF is an important factor of heterotopic ossification [6]. Objectives: To investigate the serum levels of VEGF and BMP-2 in axSPA treated with NSAIDs and their possible relationship with disease activity. Methods: 120 patients with axSPA were randomized administered with imrecoxib or celecoxib respectively for 3 months. Serum VEGF and BMP-2 were detected. ESR, CRP, BASDAI, BASFI and SPARCC were measured. Results: A statistically significant change was found in ESR, BASDAI, patients global assessment of disease activity, Schober test and SPARCC following treatment with imrecoxib or celecoxib ( P <0.05). There were no statistically significant differences between the two groups. ( P >0.05). There was statistically significant difference in serum VEGF levels before and after treatment (240.89±17.68 pg/ml vs 187.00±11.42 pg/ml, P<0.05), but no difference in BMP-2 (231.74±104.44 vs 226.80±116.26 pg/ml, P>0.05). A significant correlation was found between VEGF level and ESR, CRP, BASFI, tragus-up-wall distance and finger to floor distance, lumbar side flexion, Schober test and intermalleoar distance (r=0.628, 0.542, 0.238, 0.299, 0.353, -0.369, -0.373, -0.359, -0.274, P<0.05).And the BMP-2 levels were correlated with CRP and lumbar side flexion (r =0.213, -0.190, P<0.05). Serum VEGF levels were significantly increased in HLA-B27-positive patients than in HLA-B27-negative ones (P<0.05). Conclusions: NSAIDs can not only improve symptoms and function, but also reduce sacroiliitis possibly by affecting the levels of VEGF and BMP. Imrecoxib and celecoxib have the same efficacy.The response to treatment was correlated with the expression of HLA-B27. References: Appel H, Janssen L, Listing J, Heydrich R, Rudwaleit M, Sieper J.Serum levels of biomarkers of bone and cartilage destruction and new bone formation in different cohorts of patients with axial spondyloarthritis with and without tumor necrosis factor-alpha blocker treatment.Arthritis Res Ther;2008:10:R125. Liu KG, He QH, Tan JW, Liao GJ.Expression of TNF-alpha, VEGF, and MMP-3 mRNAs in synovial tissues and their roles in fibroblast-mediated osteogenesis in ankylosing spondylitis.Genet Mol Res;2015:14:6852–6858. Poddubnyy D, Conrad K, Haibel H, Syrbe U, Appel H, Braun J, et al. Elevated serum level of the vascular endothelial growth factor predicts radiographic spinal progression in patients with axial spondyloarthritis.Ann Rheum Dis;2014:73:2137–2143. Chen MH, Chen HA, Chen WS, Chen MH, Tsai CY, Chou CT.Upregulation of BMP-2 expression in peripheral blood mononuclear cells by proinflammatory cytokines and radiographic progression in ankylosing spondylitis.Mod Rheumatol;2015:25:913–918. Minamizaki T, Yoshiko Y, Kozai K, Aubin JE, Maeda N.EP2 and EP4 receptors differentially mediate MAPK pathways underlying anabolic actions of prostaglandin E2 on bone formation in rat calvaria cell cultures.Bone;2009:44:1177–1185. Pape HC, Marcucio R, Humphrey C, Colnot C, Knobe M, Harvey EJ.Trauma-induced inflammation and fracture healing. J Orthop Trauma. 2010 2010–09–01;24:522–5. Acknowledgements: no. Disclosure of Interest: None declared